If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = 37 + -3x Solving 8x = 37 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 8x + 3x = 37 + -3x + 3x Combine like terms: 8x + 3x = 11x 11x = 37 + -3x + 3x Combine like terms: -3x + 3x = 0 11x = 37 + 0 11x = 37 Divide each side by '11'. x = 3.363636364 Simplifying x = 3.363636364
| 15x-18y=-12 | | N*(0.01717+0.00002828*N)=1 | | 666666669998765x-2237382291982737392298273=21 | | (7-y)(5y+2)=0 | | -16t^2+148t+30=0 | | -5+-7x+-9y= | | X-X=1x+1x+x | | 11x^2+-9x=1 | | 7v^2+300=ygraph | | x(0.2+0.3x)=1 | | -(7x+9y+5)= | | (2x^2)-5x=33 | | sinx=-0.4x+1.2 | | (2x^2)-(5x)=33 | | 9*10x=17 | | y^2+2y+4=5ty^2 | | 2x+12y=-22 | | 2(3)-6=-3y | | ln(x)=56 | | 1.5y-x=-6 | | -18+9r-6r+4= | | 0=x^5+5x^4-2x^3-24x^2 | | y=4x^2+10x-4 | | 36+5t=-12-3t | | 5n-8=4n+2n | | g(c+1)=x+4 | | 2(x+3)+3x=-3(x-2)+8x | | 9.2x-18.4=8.9x-53.4 | | f(x)=6x^2+78 | | -72x=20x+92 | | 26=-68x+42x | | 6v^2-11v-35=0 |